2023
DOI: 10.1080/21645515.2023.2206278
|View full text |Cite
|
Sign up to set email alerts
|

Hesitancy, reactogenicity and immunogenicity of the mRNA and whole-virus inactivated Covid-19 vaccines in pediatric neuromuscular diseases

Abstract: The mRNA-based BNT162b2 and inactivated whole-virus CoronaVac are two widely used COVID-19 vaccines that confer immune protection to healthy individuals. However, hesitancy toward COVID-19 vaccination appeared to be common for patients with neuromuscular diseases (NMDs) due to the paucity of data on the safety and efficacy in this high-risk patient population. Therefore, we examined the underlying factors associated with vaccine hesitancy across time for NMDs and assessed the reactogenicity and immunogenicity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…17,19,80 There are minimal data on optimal immunization for those with immunocompromized conditions and comorbidities, which are absolutely necessary for protecting these vulnerable, high-risk patients. [81][82][83][84] As primary vaccination rates have peaked with satisfactory coverage in most geographical regions by this time, newer generations of polyvalent vaccines must be thoroughly investigated in the future, especially in unvaccinated infants who have not been exposed to the virus on which there is currently minimal research. 1,[49][50][51][52]85 This will be essential to inform policymakers on their decision to incorporate COVID-19 vaccines in national immunization programs.…”
Section: Discussionmentioning
confidence: 99%
“…17,19,80 There are minimal data on optimal immunization for those with immunocompromized conditions and comorbidities, which are absolutely necessary for protecting these vulnerable, high-risk patients. [81][82][83][84] As primary vaccination rates have peaked with satisfactory coverage in most geographical regions by this time, newer generations of polyvalent vaccines must be thoroughly investigated in the future, especially in unvaccinated infants who have not been exposed to the virus on which there is currently minimal research. 1,[49][50][51][52]85 This will be essential to inform policymakers on their decision to incorporate COVID-19 vaccines in national immunization programs.…”
Section: Discussionmentioning
confidence: 99%
“…This aligns with the World Health Organization’s most recent recommendation on 28 March 2023 that this high priority group should receive an additional COVID-19 booster vaccination 6–12 months after the last dose. Many older adults, young children or those with debilitating chronic diseases are hesitant towards receiving novel monovalent or bivalent mRNA vaccines due to systemic adverse effects, risks of myocarditis and potentially higher association with ischaemic stroke [ 14 , 50 52 ]. As this study demonstrated more frequent but tolerable local adverse effects only, it is possible that these individuals would be more accepting of ID inactivated vaccines.…”
Section: Discussionmentioning
confidence: 99%